A flexible composite conductive hydrogel and its preparation method and application
By introducing components such as bialdehyde nanocellulose, silver nanoparticles and urea into the conductive hydrogel, a flexible composite conductive hydrogel was prepared, which solved the problem of insufficient mechanical and electrical properties of existing conductive hydrogels, and achieved versatile and high-performance conductive hydrogels.
Patent Information
- Application Number
- CN202211631934.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The existing conductive hydrogels have problems with insufficient mechanical properties and electrical properties when converting physical signals into electrical signals, and their functions are single and cannot meet diversified needs.
A flexible composite conductive hydrogel was prepared by reacting sodium periodate with nanocellulose, mixed with silver ammonia solution, urea and silver nanowires were added, and polyvinyl alcohol and borax were added.
The prepared flexible composite conductive hydrogel has excellent mechanical properties, conductive properties, adhesion, self-healing and antibacterial properties, and is suitable for biosensors, soft robots, tissue engineering materials and other fields.
Smart Images

Figure CN115926201B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sensing materials, and in particular relates to a flexible composite conductive hydrogel and a preparation method and application thereof. Background Art
[0002] Conductive hydrogel is a gel with a network structure formed by cross-linking of polymer substances. Since the polymers in the hydrogel usually contain hydrophilic groups, they can absorb a large amount of water, which is locked in the porous gel network structure to form a hydrogel. Conductive hydrogels are rich in water, allow the exchange of oxygen and nutrient metabolites, and have viscoelastic properties similar to the human extracellular matrix (ECM). Therefore, they are used as a platform for studying three-dimensional cell microenvironments and cell interactions or as a substrate for constructing engineered tissues. In recent years, conductive hydrogels have shown great application potential in portable wearable electronic devices for medical or health care. However, in order to stably convert physical signals (including mechanical deformations such as stretching, compression or bending) into electrical signals, it is of certain practical significance to design a flexible conductive hydrogel with both excellent mechanical and electrical properties.
[0003] In addition, most traditional conductive hydrogels have single functions, cannot meet the diversified needs of advanced materials and devices, and have limited application scenarios. Therefore, it is of great significance to develop a conductive hydrogel that is ultra-flexible, highly conductive, and multifunctional (including excellent properties such as stretchability, adhesion, self-healing, and antibacterial properties). Summary of the invention
[0004] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing a flexible composite conductive hydrogel.
[0005] Another object of the present invention is to provide a flexible composite conductive hydrogel prepared by the method.
[0006] Another object of the present invention is to provide applications of the flexible composite conductive hydrogel.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a flexible composite conductive hydrogel comprises the following steps:
[0009] (1) adding sodium periodate (NaIO4) to a nanocellulose (CNF) dispersion, stirring and reacting at 35-65° C. under light-shielding conditions, adding ethylene glycol to terminate the reaction after the reaction, washing by centrifugation with water, and redispersing the washed precipitate in water to obtain a dialdehyde nanocellulose (DACNF) dispersion;
[0010] (2) dripping an ammonia solution into a silver nitrate solution drop by drop until the solution becomes clear again, thereby obtaining a silver ammonia solution; then mixing the silver ammonia solution with the dialdehyde nanocellulose (DACNF) dispersion obtained in step (1), and reacting the mixture under stirring at 70 to 95° C., thereby obtaining silver-loaded nanocellulose (DACNF@Ag);
[0011] (3) Adding binder urea and silver nanowire dispersion to the silver-loaded nanocellulose (DACNF@Ag) obtained in step (2), stirring and reacting at room temperature for 10 to 12 hours, then heating to 75 to 100° C., adding polyvinyl alcohol and borax, stirring and dispersing evenly, and then slowly cooling to room temperature to obtain a flexible composite conductive hydrogel.
[0012] The absolute dry mass ratio of sodium periodate to nanocellulose in step (1) is 4.28:0.5-1.5, preferably 4.28:0.5.
[0013] The concentration of the nanocellulose dispersion in step (1) is preferably 2% by mass.
[0014] The shading described in step (1) can be achieved by completely covering the container with tin foil.
[0015] The stirring reaction in steps (1) and (2) is preferably carried out in a constant temperature water bath.
[0016] The temperature of the stirring reaction in step (1) is preferably 50°C.
[0017] The stirring reaction time in step (1) is 1 to 5 hours, preferably 3 hours.
[0018] The amount of ethylene glycol added in step (1) is calculated so that its final concentration in the reaction system is 6% to 10% by weight volume ratio (e.g., adding 10 to 15 ml of ethylene glycol to 150 g of the oxidation system can terminate the reaction).
[0019] The conditions of the centrifugal washing in step (1) are: a speed of 8000-10000 rpm, a time of 5-10 minutes, and a number of 5-7 times; preferably: a speed of 8000 rpm, a time of 5 minutes, and a number of 5-7 times;
[0020] The temperature of the centrifugal washing in step (1) is preferably 25°C.
[0021] The water described in step (1) is preferably distilled water.
[0022] The dispersion in step (1) is preferably carried out using an ultrasonic disintegrator.
[0023] The concentration of the dialdehyde nanocellulose (DACNF) dispersion in step (1) is 1-3 wt %, preferably 2 wt %.
[0024] The concentration of the ammonia solution described in step (2) is 25% by mass.
[0025] The concentration of the silver nitrate solution described in step (2) is 1wt%.
[0026] The mass ratio of the silver ammonia solution to the dialdehyde nanocellulose dispersion in step (2) is 0.5-2.5:10-50; preferably 1.5:25.
[0027] The temperature of the stirring reaction in step (2) is preferably 90°C.
[0028] The stirring reaction time in step (2) is 1 to 6 hours, preferably 3 hours.
[0029] The absolute dry mass ratio of the binder described in step (3) to the dialdehyde nanocellulose (DACNF) is 1:1 to 5, preferably 1:1.
[0030] The mass ratio of the binder to the silver-loaded nanocellulose (DACNF@Ag) in step (3) is 1:50 to 250, preferably 1:50.
[0031] The concentration of the silver nanowire dispersion in step (3) is preferably 1 mg / mL.
[0032] The absolute dry mass ratio of the silver nanowires to the dialdehyde nanocellulose (DACNF) in step (3) is 1 to 3:100, preferably 1:50.
[0033] The heating in step (3) is preferably to raise the temperature to 95°C.
[0034] The weight average molecular weight of the polyvinyl alcohol described in step (3) is 130,000.
[0035] The absolute dry mass ratio of the polyvinyl alcohol to the dialdehyde nanocellulose (DACNF) in step (3) is 4 to 6:1, preferably 5:1.
[0036] The absolute dry mass ratio of the borax described in step (3) to the dialdehyde nanocellulose (DACNF) is 1 to 9:5, preferably 7:5.
[0037] A flexible composite conductive hydrogel is prepared by any of the methods described above.
[0038] The flexible composite conductive hydrogel is used in the preparation of biosensors, soft robots, antibacterial materials or tissue engineering materials.
[0039] The bacteria in the antibacterial material is at least one of Staphylococcus aureus and Escherichia coli; preferably at least one of Staphylococcus aureus (S. aureus) SHBCC D80431 and Escherichia coli (E. coli) SHBCC D81238.
[0040] The tissue engineering materials include human organs and the like.
[0041] Compared with the prior art, the present invention has the following advantages and effects:
[0042] (1) The filler (reinforcer) used in the process of preparing the flexible composite conductive hydrogel of the present invention is nanocellulose (CNF), which has the advantages of abundant sources, good biocompatibility, degradability, multifunctional modification and excellent mechanical properties. It shows great application potential in flexible sensors, especially wearable electronic devices.
[0043] (2) The present invention uses an in-situ polymerization method to stably and firmly attach the conductive medium, silver nanoparticles (AgNPs), to the modified nanocellulose with high reducibility. Compared with ordinary physical mixing, the combination between the two is tighter, so that the comprehensive electrical properties of the subsequently prepared composite conductive hydrogel are better. In addition, the silver nanoparticles can simultaneously give the composite conductive hydrogel excellent conductivity and antibacterial properties, that is, they have a great contribution to the multifunctionality of the hydrogel.
[0044] (3) The present invention uses urea as an additive in the process of preparing the flexible composite conductive hydrogel. The results show that urea can not only play a role equivalent to tannic acid (TA), such as promoting the connection / binding between the components in the composite hydrogel, so that the prepared hydrogel has the ability to adhere to various substrates, but also has excellent moisturizing effects, which to a certain extent prevents the volatilization of the solvent in the hydrogel (such as Figure 7 ); in addition, the amino group in urea makes it easy to form dynamically reversible hydrogen bonds with other components, which to a certain extent gives the composite conductive hydrogel self-healing properties; finally, in comparison, the cost of urea is 3 to 5 times lower than that of tannic acid, thus greatly reducing the production cost.
[0045] (4) The present invention adds borax during the preparation of the flexible composite conductive hydrogel, and the dynamically reversible boron ester bonds formed by borax give the composite conductive hydrogel better self-healing properties, which avoid the irreparable damage in traditional hydrogels, thereby greatly enhancing the durability of conductive hydrogel-based flexible sensors.
[0046] (5) The present invention uses a simple "one-pot method" to prepare ultra-stretchable, self-healing, and highly adhesive flexible composite conductive hydrogel. The method has a simple and convenient operation process, is safe and non-toxic, and is suitable for large-scale production.
[0047] (6) The flexible composite conductive hydrogel finally obtained by the present invention has multifunctional properties such as super stretchability (tensile strain can reach 4546%), strong adhesion (adhesion strength is as high as 200 kPa or more), self-healing (self-healing efficiency is as high as 99%) and antibacterial property. Therefore, it has rich application scenarios and has good development prospects in the fields of biosensors, biomedicine, soft robots and tissue engineering (such as human organs). BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a microscopic morphology of the flexible composite conductive hydrogel prepared in Example 1 of the present invention.
[0049] Figure 2 Graph showing the tensile properties of the flexible composite conductive hydrogel prepared in Example 1 of the present invention; wherein (a) is a digital photograph when testing the tensile properties; and (b) is a tensile stress-strain curve of the flexible composite conductive hydrogel.
[0050] Figure 3 Graphs showing the ionic conductivity of the flexible composite conductive hydrogels prepared in Examples 1 to 9 and Comparative Examples 1 to 3 of the present invention; wherein (a) is the ionic conductivity of the flexible composite conductive hydrogels in Examples 1 to 9; and (b) is the ionic conductivity of the flexible composite conductive hydrogels in Comparative Examples 1 to 3.
[0051] Figure 4 Graph showing the adhesion performance of the flexible composite conductive hydrogel prepared in Example 1 of the present invention; wherein (a) is a schematic diagram of the adhesion strength test method; and (b) is the adhesion strength of the flexible composite conductive hydrogel on various materials.
[0052] Figure 5 Graphs showing the self-healing performance of the flexible composite conductive hydrogel prepared in Example 1 of the present invention; wherein (a) is a digital photograph of the self-healing process after being cut; and (b) is a comparison graph of the tensile stress-strain curves of the flexible composite conductive hydrogel at the initial stage and after self-healing after being cut.
[0053] Figure 6 The diagram shows the antibacterial properties of the flexible composite conductive hydrogel prepared in Example 1 of the present invention; wherein (a) is Staphylococcus aureus; (b) is Escherichia coli (in the diagram, white is a blank group, taken from ordinary A4 paper).
[0054] Figure 7 It is the mass loss rate of the flexible composite conductive hydrogel prepared in Example 1 of the present invention and Comparative Example 1.
[0055] Figure 8 Schematic diagram of the flexible composite conductive hydrogel-based sensor of the present invention; wherein, (a) is a schematic diagram of the assembly of the sensor; and (b) is a schematic diagram of the microstructure of the flexible composite conductive hydrogel.
[0056] Fig. 9 Schematic diagram of monitoring human activities by the flexible composite conductive hydrogel-based sensor prepared in Example 1 of the present invention, wherein (a) is the monitoring of finger bending activities; (b) is the monitoring of elbow bending activities. DETAILED DESCRIPTION
[0057] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0058] Nanocellulose (CNF) involved in the embodiments of the present invention was purchased from Zhejiang Jinjiahao Green Nanomaterial Co., Ltd., with a mass fraction of 2.0%; sodium periodate (NaIO4) and sodium tetraborate (borax, Na2B4O7·10H2O) were purchased from Tianjin Fuchen Chemical Reagent Co., Ltd.; silver nitrate (≥99.8%, analytical grade) was purchased from Guangzhou Dongzheng Chemical Instrument Co., Ltd.; ammonia (mass fraction of 25%) and ethylene glycol were purchased from Guangzhou Chemical Reagent Factory. Tannic acid (TA) and silver nanowire dispersion (1 mg / mL) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; polyvinyl alcohol (PVA, M w =130,000) was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0059] The acrylic substrate involved in the embodiment of the present invention was purchased from Shenzhen Hongkunda Technology Co., Ltd., and its size is 20mm*20mm*2.0mm.
[0060] Example 1
[0061] (1) Preparation of silver-loaded nanocellulose:
[0062] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0063] ② Add 25% ammonia solution dropwise into the silver nitrate solution (1wt%) until the solution becomes clear again to obtain a silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of the silver ammonia solution with 25g of the DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0064] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0065] a. Add 0.5g urea and 10mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.5g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0066] b. Connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) with wires and pull them out, and seal them with 3M transparent tape to prevent moisture from evaporating. Specifically: Figure 8 As shown, the flexible composite conductive hydrogel is placed in the middle, clamped with an acrylic substrate, and led out with a copper electrode (copper sheet: size is 20mm*20mm*0.50mm) to assemble into a flexible composite conductive hydrogel-based sensor, which is then connected to an electrochemical workstation to obtain electrical signal output through mechanical deformation such as stretching, compression, and bending, thereby judging the sensing ability of the hydrogel-based flexible sensor.
[0067] (3) Performance testing of flexible composite conductive hydrogel and its sensor (the sample size during the tensile performance, conductivity, adhesion strength and healing performance testing was: 30×10×2mm 3 ; The size of the sample during the antibacterial performance test was a truncated cone with a radius of 4 mm and a thickness of 2 mm; The specific operation steps were carried out according to the reference: Lin F, Wang Z, Shen Y, et al. Naturalskin-inspired versatile cellulose biomimetic hydrogels [J]. Journal of Materials Chemistry A, 2019, 7 (46). DOI: 10.1039 / c9ta10502f; The experiment was repeated 3 times): The microscopic morphology of the flexible composite conductive hydrogel was observed by field emission scanning electron microscopy (FE-SEM) after freeze-drying the hydrogel (pressure of 0.05 Pa and temperature of -58 ° C) ( Figure 1 ); The tensile properties of the flexible composite conductive hydrogel were tested by a universal testing machine (Instron 5565) ( Figure 2 ); The conductive properties of the flexible composite conductive hydrogel were obtained by a digital multimeter and an electrochemical workstation ( Figure 3 ); The adhesion strength of the flexible composite conductive hydrogel on various materials (steel ruler, plastic, PVDF substrate, rubber, glass) was obtained by using the "one solution double lap specimen" method in the above reference combined with a universal testing machine ( Figure 4 ); The self-healing performance of the flexible composite conductive hydrogel was obtained by observing the self-healing speed after cutting and comparing the tensile stress-strain curve of the initial hydrogel with the tensile stress-strain curve after cutting-self-healing ( Figure 5 ); The antibacterial activity of the flexible composite conductive hydrogel was tested using two typical bacterial species: Gram-positive Staphylococcus aureus (S. aureus, strain number SHBCC D80431, purchased from Shanghai Jiachu Biotechnology Co., Ltd.) and Gram-negative Escherichia coli (Escherichia coli (E. coli), strain number SHBCC D81238, purchased from Shanghai Jiachu Biotechnology Co., Ltd.), and the antibacterial effect was determined by analyzing the diameter of the inhibition zone ( Figure 6); The flexible composite conductive hydrogel (5 g) was placed in a constant temperature and humidity chamber (Dongguan Qingsheng Testing Equipment Co., Ltd., model JQ-225-TE; temperature 25°C, humidity RH = 50%), and the mass change of the flexible composite conductive hydrogel was recorded at a certain time interval, and the mass loss rate ( Figure 7 ); The performance evaluation of the flexible composite conductive hydrogel-based sensor was obtained by monitoring the electrical signals of different human activities. For the monitoring of different human activities, the sensor showed different electrical signal outputs ( Fig. 9 ).
[0068] Example 2
[0069] (1) Preparation of silver-loaded nanocellulose:
[0070] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0071] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0072] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0073] a. Add 0.5g urea and 10mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.0g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0074] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0075] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0076] Example 3
[0077] (1) Preparation of silver-loaded nanocellulose:
[0078] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0079] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0080] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0081] a. Add 0.5g urea and 10mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 3.0g polyvinyl alcohol and 0.7g borax, stir vigorously to dissolve and disperse evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0082] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0083] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0084] Example 4
[0085] (1) Preparation of silver-loaded nanocellulose:
[0086] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0087] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0088] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0089] a. Add 0.5g urea and 5mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.0g polyvinyl alcohol and 0.7g borax, stir vigorously to dissolve and disperse evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0090] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0091] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0092] Example 5
[0093] (1) Preparation of silver-loaded nanocellulose:
[0094] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0095] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0096] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0097] a. Add 0.5g urea and 5mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.5g polyvinyl alcohol and 0.7g borax, stir vigorously to dissolve and disperse evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0098] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0099] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0100] Example 6
[0101] (1) Preparation of silver-loaded nanocellulose:
[0102] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0103] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0104] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0105] a. Add 0.5g urea and 5mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 3.0g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0106] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0107] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0108] Example 7
[0109] (1) Preparation of silver-loaded nanocellulose:
[0110] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0111] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0112] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0113] a. Add 0.5g urea and 15mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.0g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0114] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0115] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0116] Example 8
[0117] (1) Preparation of silver-loaded nanocellulose:
[0118] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0119] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0120] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0121] a. Add 0.5g urea and 15mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.5g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0122] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0123] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0124] Example 9
[0125] (1) Preparation of silver-loaded nanocellulose:
[0126] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0127] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0128] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0129] a. Add 0.5g urea and 15mL silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 3.0g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0130] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0131] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Since the other performance test results are similar to those of Example 1, only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this example are shown in Tables 1 and Figure 3 .
[0132] Comparative Example 1
[0133] (1) Preparation of silver-loaded nanocellulose:
[0134] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0135] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0136] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0137] a. Add 10 mL of silver nanowire dispersion (concentration of 1 mg / mL) to the silver-loaded nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12 hours at room temperature to mix the components evenly. Then heat the entire system to 95°C, add 2.5 g of polyvinyl alcohol and 0.7 g of borax, and stir vigorously to dissolve and disperse them evenly. After a period of time, stop heating and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0138] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0139] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this comparative example are shown in Tables 1 and Figure 3 ; The mass loss rate of the flexible composite conductive hydrogel is shown in Figure 7 .
[0140] Comparative Example 2
[0141] (1) Preparation of silver-loaded nanocellulose:
[0142] A 25% ammonia solution was added dropwise into a silver nitrate solution (1 wt%) until the solution became clear again to obtain a silver ammonia solution, which was then refrigerated in a dark environment. 1.5 g of the silver ammonia solution was mixed with 25 g of CNF dispersion (2 wt%) and placed in a constant temperature water bath at 90 ° C and stirred for 3 h to obtain silver-loaded nanocellulose (CNF@Ag).
[0143] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0144] 0.5g urea and 10mL silver nanowire dispersion (concentration of 1mg / mL) were added to the silver nanocellulose (CNF@Ag) prepared above, and stirred for 12h at room temperature to make the components evenly mixed. Then the whole system was heated to 95°C, and 2.5g polyvinyl alcohol and 0.7g borax were added to it, and stirred vigorously to dissolve and disperse it evenly. After a period of time, the heating was stopped and slowly cooled to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0145] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0146] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this comparative example are shown in Tables 1 and Figure 3 .
[0147] Comparative Example 3
[0148] (1) Preparation of silver-loaded nanocellulose:
[0149] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0150] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0151] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0152] a. Add 0.5g urea to the silver-loaded nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.5g polyvinyl alcohol and 0.7g borax, and stir vigorously to dissolve and disperse them evenly. After a period of time, stop heating and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0153] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0154] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this comparative example are shown in Tables 1 and Figure 3 .
[0155] Comparative Example 4
[0156] (1) Preparation of silver-loaded nanocellulose:
[0157] ① The aldehyde group was introduced into nanocellulose (CNF) by oxidation with sodium periodate (NaIO4) to obtain dialdehyde nanocellulose (DACNF). Specifically, 4.28g NaIO4 (final concentration of 0.13mol / L) was first added to the nanocellulose dispersion (the absolute dry mass of CNF was 0.5g), and a certain amount of water was added to make the mass of the entire oxidation system 150g. The container was completely covered with tin foil and then placed in a constant temperature water bath at 50°C, shielded from light and stirred. After the reaction continued for 3h, 10mL of ethylene glycol was poured into the above mixture to terminate the reaction. The above mixture was repeatedly centrifuged and washed with distilled water for 5 to 7 times (8000rpm, 5min, 25°C). Finally, the washed precipitate was redispersed in distilled water and dispersed using an ultrasonic crusher (SONICS VCX500, Ningbo Lawson Intelligent Technology Co., Ltd.) to obtain a dialdehyde cellulose (DACNF) dispersion with a concentration of 2wt%.
[0158] ② Add 25% ammonia solution drop by drop into silver nitrate solution (1wt%) until the solution becomes clear again to obtain silver ammonia solution, which is then refrigerated in a dark environment. Mix 1.5g of silver ammonia solution with 25g of DACNF dispersion, place in a constant temperature water bath at 90°C and stir for 3h to obtain silver-loaded nanocellulose (DACNF@Ag).
[0159] (2) Synthesis of flexible composite conductive hydrogels and assembly of hydrogel-based sensors:
[0160] a. Add 0.5g of tannic acid and 10mL of silver nanowire dispersion (concentration of 1mg / mL) to the silver nanocellulose (DACNF@Ag) obtained in step ② above, and stir continuously for 12h at room temperature to mix the components evenly. Then heat the whole system to 95°C, add 2.5g of polyvinyl alcohol and 0.7g of borax, and stir vigorously to dissolve and disperse them evenly. Stop heating after a period of time, and slowly cool to room temperature to obtain a viscous flexible composite conductive hydrogel.
[0161] b. Use wires to connect the two ends of the flexible composite conductive hydrogel (30mm*10mm*3mm) and pull it out, and seal it with 3M transparent tape to prevent water volatilization (the assembly method of the flexible composite conductive hydrogel-based sensor is the same as Example 1), and then connect it to an electrochemical workstation to obtain electrical signal output through mechanical denaturation such as stretching, compression, and bending, so as to judge the sensing ability of the hydrogel-based flexible sensor.
[0162] (3) The performance testing method of the flexible composite conductive hydrogel and its sensor is the same as that of Example 1. Only some experimental results are given here: The tensile properties and conductive properties of the flexible composite conductive hydrogel prepared in this comparative example are shown in Table 1.
[0163] Effect Example
[0164] (1) Microscopic morphology analysis:
[0165] The microscopic morphology of the flexible composite conductive hydrogel prepared in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the hydrogel presents a spatial network structure with uniformly distributed holes, that is, the structure is relatively stable. The microscopic morphology of the flexible composite conductive hydrogel prepared in Examples 2 to 9 is the same as or similar to the result of Example 1, so they are not given one by one.
[0166] (2) Comparison of mechanical properties and electrical properties:
[0167] The tensile properties and conductive properties of the flexible composite conductive hydrogels obtained in Examples 1 to 9 and Comparative Examples 1 to 4 were compared. Figure 3 And as shown in Table 1:
[0168] Table 1 Analysis of the properties of the flexible composite conductive hydrogels prepared in the examples and comparative examples
[0169] Test Project Tensile strength(kPa) Tensile strain (%) Conductivity (S / m) Example 1 498 4546 6.51 Example 2 456 4336 6.55 Example 3 520 4008 6.45 Example 4 462 4331 4.18 Example 5 480 4550 4.50 Example 6 519 4010 4.15 Example 7 447 4342 7.98 Example 8 476 4513 7.90 Example 9 505 3980 7.77 Comparative Example 1 451 3541 5.21 Comparative Example 2 466 4230 3.12 Comparative Example 3 498 4533 2.99 Comparative Example 4 367 2689 3.51
[0170] 1) It can be seen from Examples 1 to 3 in Table 1 that different addition amounts of polyvinyl alcohol (PVA) have a great influence on the tensile properties of the flexible composite conductive hydrogel. Specifically, with the increase of PVA content, the tensile strength of the hydrogel gradually increases from 456 kPa to 498 kPa and 520 kPa, but the tensile strain reaches a maximum value (4546%) when the PVA addition amount is 2.5 g (Example 1), that is, the composite conductive hydrogel obtained in Example 1 has the best comprehensive tensile properties. In addition, the conductivity of the flexible composite conductive hydrogels in Examples 1 to 3 is not much different, that is, the addition amount of PVA has little effect on the electrical properties of the hydrogel.
[0171] 2) It can be seen from Example 1, Example 5 and Example 8 in Table 1 that compared with the effect of PVA addition on the electrical properties of the flexible composite conductive hydrogel, the effect of the silver nanowire dispersion addition on the electrical properties of the flexible composite conductive hydrogel is greater. When the amount of PVA addition is unified, when the amount of silver nanowire dispersion addition is increased from 5 mL to 15 mL in an isogradient manner, the conductivity of the flexible composite conductive hydrogel increases from 4.50 S / m to 6.51 S / m and 7.90 S / m.
[0172] 3) It can be seen from Example 1 and Comparative Example 1 in Table 1 that the presence of urea has a certain effect on the mechanical properties of the flexible composite conductive hydrogel. Specifically, by adding a certain mass of urea, the tensile strength and tensile strain of the composite conductive hydrogel both show an upward trend, that is, urea has a positive effect on the mechanical properties of the flexible composite conductive hydrogel. This may be because urea acts as an adhesive, promotes the connection between the components in the composite conductive hydrogel, and improves the tensile properties to a certain extent. The presence of urea also has a positive effect on the electrical properties of the composite conductive hydrogel. Compared with the composite conductive hydrogel prepared without adding urea (Comparative Example 1), the conductivity of the composite conductive hydrogel prepared by adding a certain mass of urea is increased by 25% (5.21S / m~6.51S / m), that is, urea has a beneficial effect on both the mechanical properties and electrical properties of the composite conductive hydrogel.
[0173] 4) It can be seen from Example 1 and Comparative Example 2 in Table 1 that the modified (oxidized) nanocellulose (DACNF) is more advantageous than the unmodified nanocellulose (CNF) in the preparation of flexible composite conductive hydrogels. Specifically, the conductivity of the composite conductive hydrogel prepared from dialdehyde nanocellulose (DACNF) is much greater than the conductivity of the composite conductive hydrogel prepared from ordinary nanocellulose (CNF) as a raw material. This may be because the modified dialdehyde nanocellulose has a strong reducibility, which helps the in-situ polymerization / reduction of silver nanoparticles, and silver nanoparticles are the main conductive medium of the composite conductive hydrogel in the present invention. Therefore, the conductive properties of the composite conductive hydrogel prepared from the modified dialdehyde nanocellulose as a raw material are greatly improved.
[0174] 5) It can be seen from Example 1 and Comparative Example 4 in Table 1 that urea plays a better role in the composite hydrogel than tannic acid, so urea can be used as a potential excellent additive in the composite conductive hydrogel.
[0175] In summary, the present invention uses green, environmentally friendly, degradable nanocellulose, urea, polyvinyl alcohol, etc. as raw materials, prepares a flexible composite conductive hydrogel through a simple process, and assembles a flexible sensor based on this, which is used to monitor signals such as human activities. The present invention not only realizes a flexible composite conductive hydrogel with excellent mechanical properties and electrical properties, but also gives the hydrogel multifunctionality, including adhesion, self-healing and antibacterial properties. Therefore, it has good development prospects in the fields of biomedicine, soft robots, and human organs.
[0176] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a flexible composite conductive hydrogel, characterized in that: Including steps such as: (1) adding sodium periodate to a nanocellulose dispersion, stirring and reacting at 35-65°C under light-shielding conditions, adding ethylene glycol to terminate the reaction, washing by centrifugation with water, and redispersing the washed precipitate in water to obtain a dialdehyde nanocellulose dispersion; (2) Adding an ammonia solution drop by drop into the silver nitrate solution until the solution becomes clear again, thereby obtaining a silver ammonia solution; Then, the silver ammonia solution is mixed with the dialdehyde nanocellulose dispersion obtained in step (1), and stirred for reaction at 70-95° C. to obtain silver-loaded nanocellulose; (3) adding binder urea and silver nanowire dispersion to the silver-loaded nanocellulose obtained in step (2), stirring and reacting at room temperature for 10 to 12 hours, then heating to 75 to 100° C., adding polyvinyl alcohol and borax, stirring and dispersing them uniformly, and then slowly cooling to room temperature to obtain a flexible composite conductive hydrogel; The concentration of the dialdehyde nanocellulose dispersion in step (1) is 1-3 wt %; The mass ratio of the silver ammonia solution to the dialdehyde nanocellulose dispersion in step (2) is 0.5-2.5:10-50; The absolute dry weight ratio of the binder described in step (3) to the dialdehyde nanocellulose is 1:1-5; The mass ratio of the binder to the silver-loaded nanocellulose in step (3) is 1:50 to 250; The absolute dry weight ratio of the silver nanowires to the dialdehyde nanocellulose in step (3) is 1 to 3:100; The absolute dry weight ratio of the polyvinyl alcohol to the dialdehyde nanocellulose in step (3) is 4 to 6:1; The absolute dry mass ratio of the borax described in step (3) to the dialdehyde nanocellulose is 1 to 9:
5.
2. The method for preparing the flexible composite conductive hydrogel according to claim 1, characterized in that: The concentration of the dialdehyde nanocellulose dispersion described in step (1) is 2 wt %; The mass ratio of the silver ammonia solution to the dialdehyde nanocellulose dispersion in step (2) is 1.5:
25.
3. The method for preparing the flexible composite conductive hydrogel according to claim 1, characterized in that: The absolute dry weight ratio of the binder described in step (3) to the dialdehyde nanocellulose is 1:1; The mass ratio of the binder to the silver-loaded nanocellulose in step (3) is 1:50; The absolute dry weight ratio of the silver nanowires to the dialdehyde nanocellulose in step (3) is 1:50; The absolute dry weight ratio of the polyvinyl alcohol to the dialdehyde nanocellulose in step (3) is 5:1; The absolute dry mass ratio of the borax described in step (3) to the dialdehyde nanocellulose is 7:
5.
4. The method for preparing the flexible composite conductive hydrogel according to claim 1, characterized in that: The absolute dry mass ratio of sodium periodate to nanocellulose in step (1) is 4.28:0.5-1.
5.
5. The method for preparing the flexible composite conductive hydrogel according to claim 1, characterized in that: The concentration of the ammonia solution in step (2) is 25% by mass; The concentration of the silver nitrate solution in step (2) is 1 wt %; The concentration of the silver nanowire dispersion in step (3) is 1 mg / mL; The weight average molecular weight of the polyvinyl alcohol described in step (3) is 130,000.
6. The method for preparing the flexible composite conductive hydrogel according to claim 1, characterized in that: The temperature of the stirring reaction in step (1) is 50°C; The stirring reaction time in step (1) is 1 to 5 hours; The conditions of the centrifugal washing in step (1) are: a speed of 8000-10000 rpm, a time of 5-10 minutes, and a number of 5-7 times; The temperature of the stirring reaction in step (2) is 90°C; The stirring reaction time in step (2) is 1 to 6 hours; The heating in step (3) is to raise the temperature to 95°C.
7. A flexible composite conductive hydrogel, characterized in that: It is prepared by the method according to any one of claims 1 to 6.
8. Use of the flexible composite conductive hydrogel according to claim 7 in preparing biosensors, soft robots, antibacterial materials or tissue engineering materials.